Management of atrial fibrillation in patients with heart failure: From drug therapy to ablation - Wongcharoen W. (2014)
Atrial fibrillation (AF) and heart failure are the two modern epidemics of cardiovascular disease. They are commonly encountered together and either condition predisposes fo the other. Patients with both AF and heart failure carry a poor prognosis; therefore, the management of this group of patients should be addressed aggressively. In the context of AF management in patients with heart failure, the pharmacologic rhythm control strategy is not superior to the rate control strategy. Due to the adverse effects of anti-arrhythmic agents, the rate control should be considered as a primary approach. The long-term data regarding the efficacy and safety of catheter-based ablation therapy in the patients with heart failure are limited; hence, the catheter ablation of AF should be reserved for the patients whom the drug therapy is inadequate or undesirable. Ultimately, the patient's symptoms and the tolerance for the particular treatment should be taken into account for the management of AF in the patients with heart failure. © 2009 Expert Reviews Ltd.